EKSTRAKSI RESIN DARI BUAH JERNANG (DRAGON BLOOD) METODE UNDER KRITIS Air - Saifuddin Saifuddin (Politeknik Pertanian Negeri Kupang, 2017)
Resin jernang (dragon blood) is the world's most expensive sap. The resin obtained from jernang fruit that grows only on the islands of Sumatra and Borneo. Jernang resin is in demand by the State of China, Hongkong and Singapore, because they contain compounds that have the potential dracohordin as a medicinal ingredient in the biological and pharmacological activity such as antimicrobial, antiviral, antitumor and cytotoxic activity. The process of extracting resin jernang from fruit jernang conventionally being wet with maceration method is one way of processing fruits jernang done by people processing jernang in Bireuen Nanggroe Aceh Darussalam. However there are still significant obstacles, namely the quality of the yield is lower than the yield using methanol in the extraction process. The use of methanol as a solvent would raise the production costs due to the expensive price of the methanol and also it is not environmental friendly. This research process was using the two-stage extraction maceration method using a solvent with method sub-critical solvent.Â The price for this method was cheaper and it was also environmental friendly. The results showed that the quality of our resin jernang was better than resin jernang produced by group in Bireuen district. The class A quality based on the specification of jernang quality requirements (SNI 1671: 2010) were 73% of resin content (b / b), 6.8% of water content (w / w), 7% of ash content (w / b), 32% of impurity content (w / w), 88oC of the melting point and red colored. While the two-stage treatment requirements was between class A and super Quality with 86% of resin content (b / b), 6.5% of water content (w / w), 2.8% of ash content (w / w), 9% of levels of impurities (w / w), the melting point of 88oC and colored dark red. Keywords: Extraction, Undercritical,Â Dragon Blood, and SNI